Studi Fenomenologi Pengendalian Diri Siswa Kelas VIII SMP Negeri 21 Malang - M Ramli; Irene Maya Simon; M Ramli; Rita Raditia; Rita Raditia (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2021)
Abstract: The focus of this research is how students understand about self-control, the factors of student self-control, description of student self-control in various aspects, and the efforts of counselor which is conducted to increase student self-control. The approach used in this research is a qualitative approach with an empirical phenomenology design that involves the experience of the subject. The results obtained by researchers are in the form of descriptions of the research focus. Students view self-control as an attempt to refrain from bad things which is harmful for themselves or others. There are two factors that affect student self-control, that are the factors that come from yourself (internal) and the factors that come from outside (external). Some students have been able to control themselves quite well in various aspects, but some have not been able to control themselves well. These three aspects of self-control are reflected in the thinking patterns of students, how to make decisions, and their behavior in everyday life at school. Various efforts have been made by counselors in an effort to help students improve their self-control. These efforts are in the form of preventive efforts through information and guidance services as well as curative efforts in the form of counseling and referral services for students who have not been able to control themselves properly. Abstrak: Fokus penelitian ini adalah bagaimana pemahaman siswa tentang pengendalian diri, faktor-faktor pengendalian diri siswa, gambaran pengendalian diri siswa dalam berbagai aspek, dan usaha-usaha yang dilakukan konselor untuk meningkatkan pengendalian diri siswa. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif dengan desain fenomenologi empiris yang melibatkan pengalaman subjek. Hasil yang didapatkan peneliti berupa gambaran dari fokus penelitian. Siswa memandang pengendalian diri sebagai usaha untuk menahan diri dari hal yang buruk agar tidak merugikan diri atau orang lain. Ada dua faktor yang mempengaruhi pengendalian diri siswa yaitu faktor yang berasal dari dalam diri (internal) dan faktor yang berasal dari luar diri (eksternal). Sebagian siswa telah mampu mengendalikan dirinya dengan cukup baik dalam berbagai aspek, namun sebagiannya lagi belum mampu mengendalikan diri dengan baik. Ketiga aspek pengendalian diri tersebut tercermin dari pola berpikir siswa, cara mengambil keputusan, dan perilakunya dalam kehidupan sehari-hari di sekolah. Bermacam usaha telah dilakukan oleh konselor dalam upaya membantu siswa meningkatkan pengendalian dirinya. Usaha tersebut berupa usaha preventif melalui layanan informasi dan bimbingan serta usaha kuratif berupa konseling dan layanan referal bagi siswa yang belum mampu mengendalikan diri dengan baik.